Treatment of large chondral lesions with big bony defects: the Overlay autologous chondrocyte implantation technique - Deepak Goyal (Elsevier, 2024)
Introduction: The treatment of large chondral defects is more challenging when these chondral lesions are associated with big bony defects, which may be present in the form of either multiple subchondral (SC) cysts, or necrotic area of SC bone plate and SC spongiosa or as total fragmentation of the condylar surface. Looking to the young age of such patients, preservation of the joint is essential to prevent an early onset osteoarthritis. The marrow stimulation techniques and autologous chondrocyte implantation (ACI) need healthy SC bone to regenerate cartilage, while the osteochondral cylinder transfer techniques have donor size limitations. Objectives: A new technique to treat large chondral lesions with big bony defects is described here in step-by-step manner and is called the overlay ACI technique. Methods: The overlay ACI technique combines principles of autogenous bone grating for the treatment of large bony defects, which is followed by an overlay of ACI in a conventional manner to treat cartilage lesion. Results: The overlay ACI technique provides an autogenous solution in form of a pain-free biological joint without any sequelae to the host tissue and formation of the hyaline (like) cartilage. Conclusion: The presence of large chondral lesions with big bony defects is a surgical joint preservation challenge. The overlay ACI technique is a promising technique to treat extra-large osteochondral lesions with an autogenous solution.